Surveillance programs for early detection of hepatocellular carcinoma - Simon, Krzysztof; Serafińska, Sylwia; Pazgan-Simon, Monika (Contemporary Oncology/Współczesna Onkologia, 2012)
Primary hepatocellular carcinoma (HCC) is the most commonly diagnosed primary malignancy of the liver. The number of new diagnosed cases of HCC seems to be on a rise worldwide. HCC is typically diagnosed in patients with underlying liver cirrhosis (> 90% cases) regardless of aetiology; over a five-year follow-up period HCC develops in 15–20% of patients with cirrhosis. Patients who are at a high risk of HCC development (i.e. individuals with liver cirrhosis, especially/or chronically infected with HBV or HCV) should undergo regular screening for HCC; the current screening standard comprises liver ultrasonography and determination ofα α-fetoprotein (AFP) concentration in blood serum at ca. 6 months’ intervals (now has been excluded from current diagnostic standards). Only such diagnostic methods are capable of detecting HCC early, and thus make it possible to treat the cancer effectively.